Dynamic Characteristic Identification of Seismic-Excited Multi-Story Buildings through Response-Only Technique - Budipriyanto, Agung; Suprobo, Priyo (UI Scholars Hub, 2014)
Identifying dynamic characteristics of civil engineering structures is still a challenging task. It intends to assess behavior of the structures under time-dependent loads. This paper discusses a methodology suitable for identifying the characteristics of multi-story buildings using only their measured response under earthquake ground excitations. Appropriateness of technique used for structural identification was corroborated through coherence of the structure’s responses. The methodology was applied for identifying the characteristics of 14-story and 20-story office buildings located in a high seismic region. Responses of these two buildings recorded during three different seismic ground motions were investigated. The buildings’ response spectral densities and singular values were computed and utilized to identify their dynamic characteristics, viz. modal frequencies, damping factors, and mode types such as bending or torsion mode. Results of this study were validated through comparisons with the results reported using different structural identification techniques. It indicated that the methodology implemented in this study was capable of identifying the dynamic characteristics of multi-story buildings using responses under seismic ground motions.